Nurses Preparedness Related to Preventing Domestic Violence Against Women: Based Cross Sectional Survey - Muthia Mutmainnah; Indah Mawarti (Universitas Islam Negeri Sumatera Utara, Medan, 2022)
Violence against women and children has several very influential impacts on victims, both short term and long term such as physical, psychological and social impacts. The impact of violence on women and children can add to the problems experienced by victims and their families. Some of the physical impacts that occur on women and children who experience violence are physical injuries to the body and even death, unwanted pregnancies and declining health conditions due to permanent injuries or psychological stress. This study aims to assess the knowledge of nurses.This research is a facility-based cross-sectional study that aims to determine the level of knowledge of nurses. The sampling technique in this study was a total sampling of 56 samples, namely health workers who were directly involved in health services in Jambi City. The measuring instrument used in this study was the Physician Readiness to Manage Intimate Partner Violence Survey (PREMIS) questionnaire. Data analysis using chi square This facility based cross sectional study was carried out among 56 nursing personnel from the public sector. Two thirds of nursing personnel (67%) have moderate knowledge scores and 27% have low knowledge scores; 6% have a high knowledge score on violence. The majority of learning or knowledge needs are in the moderate category and the majority do not have the readiness to deal with victims of violence. Similar to violence against women, domestic violence is also a common occurrence. Domestic violence is common enough that it does not fail to take casualties, and the factors of domestic violence are not always big problems; it can be just a small problem but very impactful if it happens to a person who is quite emotional. Domestic violence affects women, who are always victims, and men; however, women are more likely to be victims.